2001
DOI: 10.1159/000054040
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Activates Large-Conductance Calcium-Activated K<sup>&plus;</sup> Channels and Enhances Nitric Oxide Production in Rat Mesenteric Artery and Thoracic Aorta

Abstract: Exercise training has reversible beneficial effects on cardiovascular diseases, e.g. hypertension, which may result from a decrease in systemic vascular resistance. The purpose of this study was to investigate possible mechanisms associated with the changes in vascular reactivity in large and small arteries with vasoconstrictors and vasodilators in rats after exercise. Wistar-Kyoto rats were trained for 8 weeks (Ex group) on a treadmill and compared with sedentary counterparts (Sed group). After the measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In rabbits, endurance exercise reduced renal sympathetic nerve activity, partly, due to enhanced cardiac baroreflex inhibition of sympathetic outflow to the mesenteric and renal circulation (DiCarlo et al 1997; Mueller et al 1998; De Moraes et al 2004). Moreover, in vitro studies examining the conduit arteries and microcirculation of the renal vasculature revealed enhanced production of and/or sensitivity to endogenous endothelial dilators (Chen et al 1999, 2001; Chies et al 2004; De Moraes et al 2004; Moyna and Thompson 2004). Collectively, the insignificant erythropoietic responses in our EBHD group following the static apnoea protocol might be explained by the training-induced renal adaptations and attenuation of renal vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…In rabbits, endurance exercise reduced renal sympathetic nerve activity, partly, due to enhanced cardiac baroreflex inhibition of sympathetic outflow to the mesenteric and renal circulation (DiCarlo et al 1997; Mueller et al 1998; De Moraes et al 2004). Moreover, in vitro studies examining the conduit arteries and microcirculation of the renal vasculature revealed enhanced production of and/or sensitivity to endogenous endothelial dilators (Chen et al 1999, 2001; Chies et al 2004; De Moraes et al 2004; Moyna and Thompson 2004). Collectively, the insignificant erythropoietic responses in our EBHD group following the static apnoea protocol might be explained by the training-induced renal adaptations and attenuation of renal vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%